Characteristics of Soccer Players Undergoing Primary Hip Arthroscopy for Femoroacetabular Impingement: A Sex- and Competitive Level–Specific Analysis. Issue 13 (November 2020) - Marom, Niv; Dooley, Matthew S.; Burger, Joost A.; Chang, Brenda; Coleman, Struan H.; Ranawat, Anil S.; Kelly, Bryan T.; Nawabi, Danyal H.
Background: Radiographic features of femoroacetabular impingement (FAI) are prevalent in kicking athletes, especially soccer players. However, there remains a paucity of data on the characteristics of symptomatic soccer players with an established diagnosis of FAI. Purpose: To report on patient demographics, injury, and clinical and radiographic characteristics in a large cohort of soccer players who underwent primary hip arthroscopy for FAI and to perform a sex- and competition level–specific analysis of these data. Study Design: Cross-sectional study; Level of evidence, 3. Methods: An institutional hip preservation registry containing 3318 consecutive primary hip arthroscopies for FAI performed between March 2010 and January 2016 was retrospectively reviewed for patients identified as soccer players. Patient demographics, injury characteristics, and clinical and radiographic findings were recorded, and sex- and competition level–specific differences were analyzed. Results: A total of 421 hips (336 soccer players) were identified, including 257 (61.0%) men and 164 (39.0%) women. Of these, 105 (24.9%) were reported as highly competitive, 194 (46.1%) as competitive, 75 (17.8%) as recreational, and 47 (11.2%) did not report a level. The majority of the 336 soccer players (231 hips; 55%) reported chronic hip pain lasting >6 months with no acute injury at the initial visit. Alpha angle, coronal center-edge angle, and femoral version on computed tomography scan measured 64.5°± 12°, 32.3°± 9°, and 13.7°± 10° (mean ± SD), respectively. There were 230 (55%) hips with a type 2 anterior inferior iliac spine (AIIS), 78 (18.5%) with a type 1 AIIS, and 19 (4.5%) with a type 3 AIIS. When compared with male athletes, female athletes had more hip internal rotation on physical examination (14.9° vs 8°; P < .001), lower alpha angles (57.5° vs 68.5°; P < .001), and lower-grade AIIS morphology ( P = .003). Acute injury as the reason for hip symptoms was most likely in the highly competitive group ( P < .001). Conclusion: Female soccer players were more likely to have less severe clinical and radiographic findings than were male soccer players. Acute injury as the cause of hip symptoms was more common in highly competitive players. Clinical Relevance: Focusing on soccer players with an established FAI diagnosis, the findings of this study suggest that there are sex- and competition level–based differences in the presentation, physical examination, and imaging characteristics among the players. These findings can better guide clinicians in the diagnostic evaluation of symptomatic soccer players with FAI and in tailoring treatment recommendations to specific cohorts.